A CRITICAL REVIEW AND SIGNIFICANCE OF LIPID-BASED AYURVEDIC DOSAGE FORMS GHRITA AND TAILA: PART I-REVIEW AND STATUS - BHATT, NARENDRA; DESHPANDE, MANASI (International Journal of Current Pharmaceutical Research, 2023)
This review discusses in detail one of the oldest lipid-based dosage form, Sneha Kalpana as described in Ayurved, one of the ancient medical systems. Here the vital constituents of plants are extracted as assimilates in lipid forms, ghrit–the clarified butter or taila–the oil. These dosage forms are administered through different routes for specific therapeutic benefits varying from topical nourishment, anti-inflammatory activity, and healing of tissue systems or even to treat serious neuro-muscular or neurological conditions. This review highlights the basic concepts of Ayurved behind the drug delivery approach and provides details of different processes of preparation or manufacture. Lipid-based drug delivery systems (LBDDS) are one of the emerging technologies designed to address the challenges of solubility and bioavailability of poorly water-soluble ingredients. Understanding the principles behind the processes–the right amount of heat, time, and intensity is important for standardization to ensure the availability of bio constituents. Also, it is essential to understand the relevance of therapeutic principles behind these dosage forms to choose an appropriate technological adaptation for its optimum clinical effectiveness.